1999
DOI: 10.1001/jama.282.16.1519
|View full text |Cite
|
Sign up to set email alerts
|

The Spread of the Obesity Epidemic in the United States, 1991-1998

Abstract: Obesity continues to increase rapidly in the United States. To alter this trend, strategies and programs for weight maintenance as well as weight reduction must become a higher public health priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
1,070
2
26

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,996 publications
(1,121 citation statements)
references
References 12 publications
23
1,070
2
26
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Also there are evidences to suggest that an increased body fat mass decreases postural stability and increases the odds of falling, particularly when combined with low muscle mass. Owusu et al 9 reported that hip and wrist fractures among 43 053 men aged 40-75 years was increased depending on waist circumference and waist-tohip ratio.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Also there are evidences to suggest that an increased body fat mass decreases postural stability and increases the odds of falling, particularly when combined with low muscle mass. Owusu et al 9 reported that hip and wrist fractures among 43 053 men aged 40-75 years was increased depending on waist circumference and waist-tohip ratio.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the United States, this increase has been labeled an 'epidemic' of significant public health concern due to the association between obesity and long-lasting health problems, increased disability and premature death. 2,3 Unfortunately, the concepts of overweight and obesity, as defined by body mass index (BMI), are poorly understood by the general public. Multiple investigations have documented misperceptions of weight status by adults, [4][5][6] adolescents, 7 and parents of preschool through adolescent children.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In addition to increased mortality, obesity has been known to be associated with higher risk of hypertension, diabetes, dyslipidemia and cardiovascular disease as compared to normal counterparts. 14,15 Since the prevalence of obesity has increased most rapidly among 18-to 29-year-old individuals and those with college education, 16 early intervention can help reducing the morbidity associated with obesity. In addition, the report from the third National Health and Nutrition Examination Survey has demonstrated that the prevalence of metabolic syndrome in American adolescence was 6.8% among overweight subjects and 28.7% among obese individuals.…”
Section: Introductionmentioning
confidence: 99%